Pengaruh Pelaksanaan Program Pelatihan Kewirausahaan PKK terhadap Keterampilan Berwirausaha Ibu PKK di Desa Medan Estate - Khairani, Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine the effect of the implementation of the PKK entrepreneurship training program on the entrepreneurial skills of PKK members in Medan Estate Village. A quantitative approach with simple linear regression analysis was employed. The population consisted of 25 PKK members participating in the entrepreneurship training program. Since the population was limited, all participants were selected as the sample using the saturated sampling technique. Data were collected through a questionnaire that had been validated by expert validators and confirmed to be reliable. Data analysis included descriptive statistics, the Shapiro–Wilk normality test, simple linear regression, the t-test, and the coefficient of determination (R²). The results showed that the implementation of the PKK entrepreneurship training program had a positive and significant effect on the entrepreneurial skills of PKK members, as indicated by a t-value of 3.431, exceeding the t-table value of 2.069, and a significance value of 0.002 (< 0.05). The coefficient of determination (R²) was 0.339, indicating that the implementation of the training program contributed 33.9% to entrepreneurial skills, while 66.1% was explained by other factors. It can be concluded that the implementation of the PKK entrepreneurship training program has a positive and significant effect on the entrepreneurial skills of PKK members in Medan Estate Village.